Bibo-stability of quaternionic systems - Pereira, Ricardo (2004)
The main goal of this paper is to characterize BIBO-stability of input/output quaternionic systems. After defining and investigating properties of quaternionic polynomials and rational functions, the Smith and the Smith-McMillan forms of quaternionic matrices are studied. Finally, the stability of quaternionic behavioral systems is analyzed using these tools.